2018
DOI: 10.1007/jhep06(2018)037
|View full text |Cite
|
Sign up to set email alerts
|

Dark matter direct detection from new interactions in models with spin-two mediators

Abstract: We consider models where a massive spin-two resonance acts as the mediator between Dark Matter (DM) and the SM particles through the energy-momentum tensor. We examine the effective theory for fermion, vector and scalar DM generated in these models and find novel types of DM-SM interaction never considered before. We identify the effective interactions between DM and the SM quarks when the mediator is integrated out, and match them to the gravitational form factors relevant for spin-independent DM-nucleon scat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…In Refs. [17][18][19]23] it was however shown that, for DM masses larger then the KKgraviton mass, another annihilation channel opens, namely DM annihilation into two (identical) KK-gravitons, σ(DM DM → G n G n ). In this paper, we have studied the possibility that this channel may give a cross-section large enough to attain the observed relic abundance, for the particular case of a scalar DM particle with mass m S .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Refs. [17][18][19]23] it was however shown that, for DM masses larger then the KKgraviton mass, another annihilation channel opens, namely DM annihilation into two (identical) KK-gravitons, σ(DM DM → G n G n ). In this paper, we have studied the possibility that this channel may give a cross-section large enough to attain the observed relic abundance, for the particular case of a scalar DM particle with mass m S .…”
Section: Discussionmentioning
confidence: 99%
“…The total cross-section for spin-independent elastic scattering between dark matter and nuclei reads [23]:…”
Section: Direct and Indirect Dark Matter Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…1112 In this paper we provide a detailed account of the calculations reported in [19,20], specifying all conventions 11 Spin-2 KK mode scattering was previously considered by [46], which used deconstruction to prove that the KK mode scattering amplitudes grew no faster than O(s 3 ) for a flat extra dimension. 12 Following the appearance of [19], and as [20] was being completed, the authors of [47] independently proved that the scattering amplitudes of helicity-zero modes of massive spin-2 KK modes in extra-dimensional theories grow only like O(s) for compactifications on arbitrary Ricci-flat manifolds. Their proof does not encompass the case of RS1, which is the focus of our work.…”
Section: A Scattering Of Single Massive Spin-2 Particlementioning
confidence: 99%
“…[19,20] and subsequently studied in Refs. [21][22][23][24][25]. The generic conclusion of these papers was that when all the matter content is localized in the so-called TeV (or infrared brane), after taking into account current LHC bounds it was not possible to achieve the observed Dark Matter relic abundance in warped models for scalar DM particles (whereas this was not the case for fermion and vector Dark Matter).…”
mentioning
confidence: 99%